Differences of cognitive function between genders among university students / Sarah Nabahah Ismail ... [et al.] - Ismail, Sarah Nabahah; Nural Azhan, Mohd Azim; Syed Omar, Syed Shahbudin; Miswan, Mohd Syafiq; Zainuddin, Nurul Farha (Faculty of Sports Science and Recreation, 2024)
Differences in cognitive ability and brain anatomy have been observed between genders, attributed to a combination of genetic, hormonal, and environmental factors. It is important to note that these variations do not imply any overall superiority of one gender over the other. Previous research has explored inhibition capacities and gender-specific differences in risky decision-making. The central question remains: do men or women excel in specific cognitive activities? This study aimed to compare the cognitive function between males and females among university students. A convenience sample of 42 university students (21 female, 21 male) voluntarily participated in this study. A Stop Signal Task was used to assess the cognitive performance of the participants. The stop-signal paradigm explored motor inhibition in a laboratory setting using a computerized test. Visual cues were used in the task. The computerized test used E-Prime 3.0 software and all the data was merged using E-Merge 3 and E-Data Aid 3. The Statistical Package for the Social Sciences (SPSS) version 26 was performed independent sample t-test to analyze all the data. Results showed that there are no significant differences in cognitive function between both genders. Regardless of the mean differences for reaction time and accuracy, the p-value was greater than 0.05 and proved that there are no significant cognitive function differences. Uncertainty still exists regarding the correlates of the cognitive differences between the genders. The limitations arising from the convenience sample size may restrict the generalizability of the findings to the broader population of university students. Future studies might focus on other populations particularly gender differences. Specifically, enhancing the Stop Signal Task to more closely replicate real-world human activities related to inhibitory control could be beneficial. In conclusion, this study has yielded important findings of inhibition ability between female and male of university students.